Revised Test of Precipitation Forecasting Product of RMAPS-ST System Based on U-Net - Hua, Gao; Jie, Liang; Dongling, Bao; Wang, Zaiwen; Qi, Yajie; Zuofang, Zheng (European Journal of Applied Sciences, 2024)
Using the U-Net algorithm idea in the field of artificial intelligence, a deep learning framework is designed and the loss function is redefined. This learning framework revised the precipitation forecast results of RMAPS-ST after training on two summer samples. Approved the revised precipitation forecast for June-July 2022 and precipitation on August 18, 2022, The test results show that the revised forecast level is significantly improved, especially for magnitude greater than 0.1mm/3 hours, and the CSI score is increased by an average of 30% compared with before revision.